An autonomic mechanism based on ant colony pattern for detecting the source of incidents in complex enterprise systems. (18th July 2019) - Yaghoobirafi, Kamaleddin; Nazemi, Eslam
In complex enterprises, various events such as failure of a server, malfunction of an application etc. may happen. In many cases, these events are caused by a change or an incident in a resource which belongs to another layer of information technology architecture. This makes the detection of complex events very difficult. In this paper, a mechanism is proposed based on pheromone deposition pattern for detecting the main source of failures and deficiencies in any position in the information technology architectural layers and recognising appropriate alternative solutions. It is expected that this mechanism facilitates the coordination between the resources which are not digitally represented. For sake of evaluation, two case studies are considered which investigate the inter-layer adaptation scenarios. The results show that the adaptation process can be done in less time and with more scalability with utilisation of the proposed mechanism in comparison with classic approaches.